Formulation of the Proposed Regional Regulation (Raperda) on Islamic Boarding Schools in Salatiga City after the Ratification of Law No. 18 of 2019 concerning Islamic Boarding Schools in the Era of Regional Autonomy - Dardiri, Ahmadi Hasanuddin; Miftahuddin, Mifathuddin (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2021)
This research discusses the formulation of the proposed Raperda in Salatiga City which until now has not published the Raperda Pesantren as a mandate from Law no.18 of 2019 concerning Islamic Boarding Schools. This research is expected to be a guide for the Salatiga city government in making the Raperda Pesantren so that it does not conflict with the spirit of the issuance of the Pesantren Law. This study uses an empirical juridical method by analyzing the attribution of the Islamic boarding school law to the local government in a juridical context and conducting interviews with data sources related to the non-accommodation of the regional regulation on boarding schools in Salatiga City. The results of this study conclude two things. First, the Raperda of Islamic Boarding Schools in Salatiga City has not been accommodated because the Salatiga City Government believes that Islamic boarding schools are religious matters that cannot be autonomous, or are not educational matters. Second, the formulation of the proposed Raperda in Salatiga City covers 3 main things, namely: 1) the involvement of the Salatiga City Government in the provision of education by facilitating cottages or dormitories and mosques or prayer rooms; 2) the involvement of the Salatiga City Government in the Islamic boarding school's missionary function; and 3) the involvement of the Regional Government in the function of community empowerment.